Invasive Haemophilus influenzae disease. Spain 2023 (Boletín Epidemiológico Semanal, 2024)
Introduction: Epidemiological analysis of invasive Haemophilus influenzae disease (IHD) in Spain during 2023 and its comparison with previous years (2015-2022).Method: Descriptive epidemiological analysis of IHD cases reported to the National Epidemiological Surveillance Network (RENAVE) in 2023. The variables analyzed were: sex, age group, date of onset of symptoms, reporting region, death, clinical manifestation, and serotype.Results: In 2023, 674 cases of IHD were reported (54% men) with a cumulative incidence rate of 1.39 (number of cases per 100,000 inhabitants). The highest incidence rates in 2023 were observed in children under 1 year of age and in the population aged 85 years and over. During this year, the typical seasonal pattern of this disease was recovered, with a higher number of cases of IHD in autumn and winter. The most frequent clinical manifestation, regardless of age, was bacteremic pneumonia (27.9% of cases). 80.4% of deaths occurred in the 65-year-old age group. The serotype of most reported cases of HIE is unknown.Discussion: In 2023, the highest cumulative incidence in the last 9 years was recorded. Improved reporting of microbiological characterization data is crucial for conducting surveillance of this disease and for evaluation of the vaccination program.
Keywords: Invasive disease by Haemophilus influenzae; Haemophilus influenzae; Spain; Epidemiological analysis; 2023